PENDAPATAN USAHA TERNAK AYAM BROILER DI DESA KAPUH KECAMATAN SIMPUR KABUPATEN HULU SUNGAI SELATAN PROVINSI KALIMANTAN SELATAN - Bahrun Bahrun; Zuraida Zuraida (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
This research is technically aimed at knowing the economic operation of broiler chicken cultivation regarding costs, income and business income of broiler chickens in Kapuh Village. The method used in this research is descriptive qualitative research method. Determination of respondents was carried out by case method to 1 (one) farmer working on broiler chickens in Kapuh Village, Simpur District, Hulu Sungai Selatan Regency, South Kalimantan Province as respondent farmers.  Broiler chicken farming which is carried out by an independent livestock business, the breeder provides himself with all the equipment and production inputs starting from the provision of land and cages, seeds to harvesting and selling. The explicit costs of animal husbandry include costs of production facilities, depreciation of tools and labor outside the family (TKLK) with an average of Rp. 79,900,000.00. The average production obtained was 4,004 heads or 6,406.40 kg, while the price at the time of research / harvest was IDR 20,000 / kg. Receipt of Rp. 128,128,000.00 and an income of Rp. 43,503,500.00